Non-standard Features of the Slovene Language in Slovene Popular Culture - Valh Lopert, Alenka; Koletnik, Mihaela (2018)
The monograph provides an overview of the authors’ ten-year joint research and the results of linguistic analyses carried out on samples from various media: film, theatre, radio and popular music. Some of the research has aleady been presented at conferences and consequently partially or completely published in Slovene or English. Overall, they have paid particular attention to Non-standard social varieties, from regional colloquial language and urban language to the dialects of north-eastern Slovenia. The work thus combines dialectological and sociolinguistic studies, emphasising the importance of selecting an appropriate linguistic variety for public use, whether that use is to broadcast on the radio, to express oneself in song lyrics or to flesh out a character in a film or play.
Keywords: popular culture; Non-standard language; regional colloquial language; dialect; film; theatre; radio; music